Idiopathic gestational gigantomastia: a case report - Basri, Nurul Iftida; Mohd Tamrin, Mohd Islahuddin; Zulkifli, Nur Adila; Loke, Xi-Mun (Royal Thai College of Obstetricians and Gynaecologists, 2025)
Background: Gestational gigantomastia (GGM) is described as a diffuse and rapid enlargement of the breasts during pregnancy. It is a rare condition with an incidence of 1 in 28,000 to 1 in 100,000 pregnancies worldwide. Case presentation: We present a case of a 29-year-old lady, G2P1 at 15 weeks gestation who presented with 2-months history of painful bilateral breast swelling. Clinical examination revealed erythematous bilateral breast enlargement. Results of multiple breast biopsies range from lactational adenoma and acute on chronic mastitis changes. She was treated with multiple courses of antibiotics for bilateral cellulitis with mastitis, however both breasts continued to enlarge. The revised diagnosis of gestational gigantomastia was made and she was started on steroid. Nevertheless, she failed to respond. Oral Bromocriptine commenced at 29 weeks showing some reduction in her breasts size. The fetus was however found to have a growth restriction requiring delivery at 37 weeks. Her breast has reduced by half of the initial volume during postnatal review. She was offered bilateral reductive mammoplasty and mastopexy, but she was not keen and opted for conservative management. Conclusion: A thorough investigation is necessary to rule out other causes in women presenting with gigantomastia in pregnancy. GGM treatment ranges from conservative, hormonal therapy, reduction mammoplasty, mastectomy with or without reconstruction. This depends largely on the severity of disease and the patient’s wish.